Clinical Factors Related to Histopathologic Grade in Meningioma - Kristiani, Erna; Agelica, Michelle; Suharyani, Sally; Dharmawan, Kevin (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Background: Meningiomas are the most common intracranial tumor of central nervous system tumors. Although the prevalence is lower, the WHO grade II and III meningiomas are more aggressive, with higher mitosis rates, are more likely to recur after surgery, and have lower survival rates. The ability to differentiate between WHO I and WHO II/ III meningiomas before surgery can contribute to a significant clinical benefit in helping the neurosurgeon doing the best management planning.Methods: This is a retrospective cross-sectional study of meningioma patients in Siloam Hospital Lippo Village between 2014 – 2018. The sample will be recruited using consecutive sampling. The relationship between analyzed variables and meningioma grades will be investigated using a chi-square test if the data was eligible; otherwise, the Fisher-exact test will be performed.Result: Ninety eight (69%) patients diagnosed as low grade meningioma, and 44 (31%) as high grade meningioma. Tumor location, size, edema, necrosis, age, and gender had significant results with p £0.05. Multivariate results also show that all six variables have a significant relationship with each other.Conclusions: Tumor location, size, edema, necrosis, age, and gender have a significant relationship to histopathological meningioma grade in patients at Siloam Hospital Lippo Village in 2014-2018.